1861 Ga. Code 858 - (:unkn) unknown (My University, 1861)
§4413: Prohibited the concealed carry of any pistol, dirk, sword-cane, spear, Bowie-knife, or any other kids of knives manufactured for offense or defense. Violators guilty of a misdemeanor
Keywords: CARRY - CONCEALED